Linking the trust of industrial entrepreneurs on elements of ecosystem with entrepreneurial success: Determining startup behavior as mediator and entrepreneurial strategy as moderator - Rehman, Zia Ur; Arif, Muhammad; Gul, Habib; Raza, Jamshed (Frontiers in Psychology, 2022)
Purpose This study aimed to apply “multi-criteria decision approach and attitude-change theory” to examine post-COVID-19 impact on entrepreneurial mindset by investigating the link between entrepreneurs social capital (trust on three elements of ecosystem i.e., experts & enterprises, media, and government) and entrepreneurial success (both individual and organizational). Specifically, this study analyzed entrepreneurs' dispositional factor (startup behavior) as an underlying mechanism to bridge trust and entrepreneurial success. Furthermore, it also analyzed entrepreneurs' situational factor (entrepreneurial strategy) as boundary condition. Design/methodology/approach We applied time-lagged data collection from 505 industrial entrepreneurs. Survey method was used for data collection. A 7-point Likert scale was used for the respondent response. Hayes developed PROCESS models 4 and 7 were used to test the hypothesis. Findings The direct impact of trust on three elements of the ecosystem was found significantly positive on both startup behavior and entrepreneurial success. The direct impact of startup behavior on entrepreneurial success is also significantly positive. The impact of startup behavior on indirect mediation between trust and entrepreneurial success is visibly positive. The moderated and moderated mediation impact of entrepreneurial strategy found positively significant at low and medium values. However, this study found an insignificant moderated impact at high values of entrepreneurial strategy between trust on media and startup behavior. Furthermore, this study also found insignificant moderated mediation impact at high values of entrepreneurial strategy by interacting with two elements of ecosystem (trust on media and trust on government) through startup behavior on entrepreneurial success. Originality/value The authors suggested that startup behavior is an underlying mechanism through which industrial entrepreneurs trust achieved desired entrepreneurial success. The authors also suggested that the influencing role of “low level of entrepreneurial strategy” in comparison with “high level entrepreneurial strategy” is more helpful to achieve entrepreneurial success. Implications This study contributed to the literature on entrepreneurial strategy for its conditional indirect moderated impact on startup behavior and moderated mediation impact on firm entrepreneurial success. It also contributed to owners of the manufacturing industry for their startup behavior as an underlying mechanism through which trust influences entrepreneurial success.